Protein expression of matrix metalloproteinase (MMP-1, -2, -3, -9 and -14) in Ewing family tumors and medulloblastomas of pediatric patients - Mateo, Elvis Cueva; Motta, Fabio José Nascimento; Queiroz, Rosane Gomes de Paula; Scrideli, Carlos Alberto; Tone, Luiz Gonzaga (Journal of Pediatric Genetics, 2012)
The matrix metalloproteinases (MMP) are endopeptidases performing proteolytic functions in the extracellular matrix and their overexpression has been suggested to be a characteristic of malignant tumors. Molecular changes such as the presence of chimeric protein Ewing’s sarcoma protein-friend leukemia virus integration 1 (EWS-FLI1) in the Ewing family of tumors (EFT) and the oncogenes C-ERBB-2, N-MYC, C-MYC in medulloblastoma (MB) promote the overexpression of MMP. In the present study, protein expression of MMP-1, -2, -3, -9 and -14 was qualitatively evaluated in 17 EFT and MB samples of children and adolescent by western blotting and optical densitometry, and the level of gene expression of some MMPs was determined by real-time quantitative polymerase chain reaction. Five MB samples (45.4%) presented expression of the five MMPs and six samples (54.6%) presented expression of at least one of them. Four EFT samples (66.6%) presented expression of MMP-2, -9 and -14, and two samples (33.4%) presented expression of at least one of these MMPs, whereas the presence of MMP-1 and -3 was not observed. Gene analysis showed that MMP-2 had a high expression in MB, while the expression of MMP-9 and MMP-14 was higher in EFT. It has been established that the expression of the MMPs might be related to a complex pathway of gene regulation.
Keywords: Matrix metalloproteinase; Ewing tumors; medulloblastomas; protein expression